The relationship between intellectual capital, innovation capability with firm age and firm performance - Muhammad Arafat, Noordin (2014)
The recognition of intellectual capital and innovation capability as a key success factor in an increasingly competitive, global economy has the groundwork for researchers to explore new practices of management. Intellectual capital is defined as a combination of human, structural and relational capital that creates value and consequently determines the performance of a firm whilst innovation capability refers to the ability of a firm to transform an idea into a something new which carries an economic value. The study focuses on small and medium enterprises because they make up the bulk of firms in the Malaysian economy and the Government has spent a lot of money, time and effort to develop them. The study begins with an extensive literature review concerning the research problems and issues, theoretical concept, definition and measurement of intellectual capital, human capital (HC), structural capital (SC), relational capital (RC), innovation capability, firm age and firm performance. Next, using the survey data collected from small and medium enterprises, it provides a comprehensive set of empirical evidence that look into the mediating role of innovation capability and the moderating role of firm age in the relationship between intellectual capital, HC, SC, RC and firm performance. There are three conclusive findings of the study. First, intellectual capital, RC and innovation capability have influence on performance; second, intellectual capital and SC have influence on innovation capability; and third, innovation capability mediates the effect of intellectual capital and SC on firm performance. Based on these findings, the researcher lists several recommendations in the form of management science that can be used by policy-makers and business owners to improve business performance. Finally, this study highlights the limitations of the study and suggests directions for future studies.